KEABSAHAN PENERBITAN SURAT IZIN PERTAMBANGAN DAERAH KOMODITAS TAMBANG GOLONGAN BATUAN DI KOTA SAMARINDA - Sayid ahmad aulia nur (Journal of Law ( Jurnal Ilmu Hukum ), 2014)
ABSTRACT            One of the natural richness that exist in almost all regions of Indonesia is a mineral excavation class C. Class C material is intended in the category of non- strategic minerals and vital. As minerals are not strategic and vital, the authority granting the mineral category C, since the reign of centralized to decentralized period, are at the local government. Samarinda city geologically is an area that potentially has significant materials, such as minerals category C, such as urug soil, clay, sand and so on. In some locations these minerals have endeavored to mining stage, either by foreign firms and domestic firms or by local people.            In the preamble weigh Act No. 4 of 2009 on Mineral and Coal stated that the mineral and coal mining law contained in the region of Indonesia is a non-renewable natural resources as the gift of God Almighty who has a role in meeting the livelihood of many people because it management should be controlled by the state, to provide added value for certain and evident to the growth of the national economy in order to achieve prosperity and welfare of the people equitably.            Mining Permit (SIPD) Samarinda city still adhere to the old local regulations and decisions Samarinda Mayor earlier, prior to the issuance of Law No. 4 of 2009 on Mineral and Coal. The reasons are still using the old rule is because there is a new issuance of regional regulations governing mineral and coal mining in Samarinda, so that the old rules are still used in the implementation of the mining permit in the city of Samarinda.            Government should Samarinda through Integrated Licensing Service Agency, immediately revoke the mining license area is excavated materials issued Class C post enacted Law No. 4 of 2009, and no longer issuing new Regional Permit Penembangan or extension before the relevant local legislation by Act No. 4 of 2009, and the Department of Industry, Trade, Mining and Energy Samarinda City should not issue recommendations Regional Mining Permit issuance minerals group with C. Samarinda City Government Legislative Council as soon as possible Samarinda revise Bylaw No. 17 of 2008 in order to be adapted by Act No. 4 of 2009 on Mineral and Coal, in order to avoid conflict between the laws which are above the regional regulation.